MARKAZIY OSIYODA ENERGETIKA SOHASIDAGI NIZOLARNI HAL QILISHDA ARBITRAJNING O'RNI (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article presents important issues and proposals on the importance of arbitration institutions in resolving disputes arising in the energy sector, i.e., disputes arising between states, contractual and non-contractual disputes in the countries of Central Asia such as Uzbekistan, Kazakhstan, Turkmenistan, Tajikistan, and Kyrgyzstan, as well as their importance in resolving disputes.